Comparisons of Retinal Nerve Fiber Layer Thickness after Indocyanine Green, Brilliant Blue G, or Triamcinolone Acetonide-Assisted Macular Hole Surgery - Yoshiharu Toba; Shigeki Machida; Daijiro Kurosaka (Journal of Ophthalmology)
Purpose. To compare the postoperative changes of the retinal nerve fiber layer (RNFL) thickness in patients with macular holes (MHs) treated with vitrectomy with indocyanine green- (ICG-), brilliant blue G- (BBG-), or triamcinolone acetonide- (TA-)assisted internal limiting membrane (ILM) peeling. Methods. Sixty-one eyes of 61 consecutive patients with MHs were studied. Each eye was randomly selected to undergo either ICG- (n=18), BBG- (n=21), or TA-assisted (n=22) ILM peeling. The circumferential retinal nerve fiber layer (RNFL) thickness was determined by spectral-domain optical coherence tomography (SD-OCT) before and 1, 3, 6, 9, and 12 months postoperatively. The mean overall and the sectoral thicknesses of the RNFL were obtained for each group. Results. A transient increase of the RNFL thickness was seen in the mean overall and sectoral thicknesses except for the nasal/inferior sector at 1 month after surgery for the three groups. Then, the thickness gradually decreased and returned to the baseline level in all sectors except for the nasal/inferior sector. The differences in the RNFL thickness among the groups were not significant for at least 12 months postoperatively. Conclusions. The degree of change of the RNFL thickness was not significantly related to the type of vital stain used during MH surgery.